Sacred, Memory and Rite - Elton Moreira Quadros (Caminhos)
Abstract: we reflect on the characteristics of the sacred in its relationship to memory and how this relationship occurs especially in the Catholic rite. For that, we dialogue with the work of Mircea Eliade and Rudolf Otto, with the Jewish interpretations of moments in which memory and the sacred meet and their displacement and reinterpretation in Christianity